Analysis of Delays in Inheritance Distribution from the Perspective of Islamic Law and Customary Law in Jebres Village, Surakarta: Analisis Penundaan Pembagian Warisan Perspektif Hukum Islam dan Hukum Adat Di Kelurahan Jebres Surakarta - Husna, Lutfia Miftakhul; Wibowo, Muhammad Kurniawan Budi; Pradana, Aditya Fajri Kurnia (JAS : Jurnal Ahwal Syakhshiyyah, 2024)
Inheritance is the transfer of rights to the heir's property to the heirs and is a natural process that occurs when someone dies. In practice, there are people who delay the distribution of inheritance for various reasons. This study aims to analyze the delay in the distribution of inheritance in the perspective of Islamic law and customary law in Jebres Village, Surakarta. This is considered important because although there is no text that explicitly prohibits delaying the distribution of inheritance, it may conflict with other texts. However, there are opinions that allow delays in the distribution of inheritance from the perspective of maqosyidus shari'ah, namely the existence of benefits. Traditionally, delays usually occur due to waiting for the heirs to gather or deliberately delayed and not distributed because it is believed that the strength and integrity of the household will be maintained even though the inheritance is not distributed. The research method used is qualitative, the data used is collected through interviews with families who make delays, reinforced by documentation from the parties involved and literature studies to add to the study in the research process. The results showed that the delay in the distribution of inheritance that occurred in Jebres Village was due to several factors, namely the mixing of husband and wife's assets so that it was difficult to separate, the presence of living parents, high selling prices and the main factor of lack of understanding of faraid science.